CHALLENGES AND OPPORTUNITIES IN ADULT EDUCATION IN GREENLAND - Ahrens, Andreas; Zascerinska, Jelena; Aleksejeva, Ludmila; Gukovica, Olga; Zascerinskis, Mihails; Aleksejeva, Anastasija (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
Education in Greenland is a central parameter in achieving the long-term goals of the Government in terms of providing the population with the necessary means to take up positions as skilled labour. The research aim is to implement theoretical and empirical analysis of adult education in Greenland underpinning the identification of challenges and opportunities in adult education in Greenland. The empirical study of the exploratory nature was carried out in November-December 2020. Data collection was based on document analysis as well as interview. The obtained data were processed via content analysis. Findings of the theoretical analysis allow defining challenges as externally created problem situations. The structuring content analysis allows identifying challenges and opportunities in adult education in Greenland. The summarizing content analysis reveals that adult education within the educational system in Greenland has not been properly addressed. The empirical findings allow concluding that adult education in Greenland is to be shaped in such a way that it responds to the emergent challenges. The present study has some limitations. The new research question has been formulated: What modern skills (creativity, digital skills, entrepreneurship, languages, etc) do adult learners in Greenland need most? Future research will focus the extension of the dataset.